HUBUNGAN PENGGUNAAN AKDR DENGAN DERAJAT KEPUASAN SEKSUAL PADA PASANGAN SUAMI ISTRI USIA REPRODUKSI - SORAYA HUMAIRA; RAHMANITA SINAGA (JURNAL ILMIAH SIMANTEK, 2023)
Family planning is an effort to regulate the birth distance of children and the ideal age of childbirth to create a quality family. In 2011, BKKBN has prioritized the use of IUDs (Intrauterine Devices) as one of the strategic steps to improve long-term contraceptive methods (MKJP). Sexual function can be affected by age, knowledge, chronic diseases, sexual hormones, pregnancy, and childbirth. The use of IUDs can have an effect on sexual function. The purpose of this study was to determine the relationship between IUD use and the degree of sexual satisfaction in married couples of reproductive age. This study was a cross-sectional study. This study was a cross-sectional study. The number of samples was calculated using the Lemeshow formula amounting to 30 samples where 30 couples were married couples who used IUD and 30 couples who did not use IUD as a control, so the number of samples was 60 married couples. The hypothesis test used is the Chi Square Test. Data were collected using NSSS questionnaires. Based on the Chi Square test, there is a significant relationship between the use of IUD and the degree of sexual satisfaction in married couples of reproductive age where the P value is 0.000 (<0.05). There was a significant association between IUD use and the degree of sexual satisfaction in married couples of reproductive age.